A retrospective observational study to assess the maternal and neonatal outcomes with instrumental delivery in tertiary care hospital - Nayak, Kavitha D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In modern obstetrics, the number of vaginal deliveries is reducing, and instrumental delivery are still reduced. This could be due to need for obstetrician skill for instrumental delivery, increased perineal tears or foetal injuries. The objective of this study was to assess the maternal and neonatal outcomes with instrumental delivery. Methods: This is a retrospective observational study conducted in tertiary care hospital from January 2023 to December 2023. In this study, 31 cases of forceps delivery and 15 cases of vacuum were studied for maternal and neonatal outcomes. Results: The total number of deliveries were 2693 and vaginal deliveries were 999 and instrumental deliveries were 46. It was observed that most patients (86.9%) requiring instruments in the second stage were primigravida. The most common indication for instrumental delivery is both fetal distress and poor maternal bearing down efforts. The maternal complications were more with forceps and included extension of episiotomy in 5 cases, third degree perineal tear in 6 cases, 2 cases of hematoma- one case of broad ligament hematoma and 2 patients required blood transfusion. The neonatal complications were more with forceps. However, the outcomes were favourable. We did not have any case of HIE stage 3, no baby required intubation. 3 babies with forceps had poor Apgar at birth and HIE stage 1. Conclusions: Instrumental delivery is relatively a safe and good option provided all the criteria are met. With proper technique, we can reduce the maternal complications as well.